Intermediate Microeconomics : A Modern Approach - Varian, Hal R. (New York W.W. Norton)
This edition continues the title's contemporary emphasis and is aimed at students studying microeconomics in their first or second years. It provides fresh insights into information technology, expanded coverage of strategic behaviour and a new chapter on auctions featuring fresh research.
Include Index and Appendix.
Keywords: Microeconomics